2021
DOI: 10.3390/su14010245
|View full text |Cite
|
Sign up to set email alerts
|

Research on Global Grain Trade Network Pattern and Its Driving Factors

Abstract: Trading systems are essential in promoting global food security. With the growing proportion of global food consumption obtained through international trade, the global food trade pattern has become increasingly complex over recent years. This study constructed a weighted global grain network using the trade data of 196 countries in 2000 and 2018 to explore the structure and evolution based on the complex network theory. We established that the global grain network was scale-free. There was significant heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
4
16
0
Order By: Relevance
“…Therefore, there is a trade demand between these countries [52]. Since income level affects the structure of food consumption, higher income levels not only increase the general level of food consumption but also the demand for protein foods in the dietary structure of the population [35]. Therefore, the smaller the income difference, the more likely it is that trade will occur.…”
Section: Qap Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a trade demand between these countries [52]. Since income level affects the structure of food consumption, higher income levels not only increase the general level of food consumption but also the demand for protein foods in the dietary structure of the population [35]. Therefore, the smaller the income difference, the more likely it is that trade will occur.…”
Section: Qap Analysis Methodsmentioning
confidence: 99%
“…Consistent with these studies, scholars attach weights to the trade network since they analyze the topology of the trade network and infer that the country's GDP, trade policies, and other factors affect the global trade network [32][33][34]. Presently, complex network analysis methods have been widely used in international trade, focusing on energy and agricultural products [35][36][37][38][39], with relatively less focus on the dairy products' trade network pattern.…”
Section: [29]mentioning
confidence: 99%
See 1 more Smart Citation
“…Li and Li (2022) revised the model, considering the heterogeneity of workers in terms of skills and liquidity, it is easier to analyze the regional asymmetric trade cost problem. Duan et al (2021) found that the gravity model modified from the original "core-periphery" model can better depict reality, using Spanish migration data. Asadi and Jafari Samimi (2022) studied the social desirability of agglomeration and the efficiency of policy intervention and found that under the condition that the trade cost is in the middle level, there is a stable equilibrium of partial agglomeration of enterprises in addition to the "core-periphery" equilibrium.…”
Section: The Core-periphery Theory Of Urban Resource Efficiencymentioning
confidence: 99%
“…The network density, trade scale, and agglomeration degree increased, showing an increasingly "small-world" characteristic [25]. The network pattern evolved from the unbalanced pattern of United States dominance and few discrete cores to the balanced pattern of multi-core agglomeration with Russia, the United States, Thailand, and other important grain-exporting countries [26,27]. In addition, Ying et al [28] previously presented a useful demonstration.…”
Section: Introductionmentioning
confidence: 99%